Traffic Injuries Issue in Romania - Tomescu, Cristina; Casapu, Alin (Calitatea Vieții, 2009)
This study raises the problem of traffic injuries in Romania, as recent statistical data show that, as compared to EU average, East European countries have a significantly higher mortality rate by accident injuries at similar ratio of passengers. In terms of social costs, the increase of traffic accidents rate means a higher social burden and also a higher financial burden for health services and social assistance. The sudy argues, therefore, that the problem of traffic safety is an important social problem that should be discussed not only by Police specialists but also by sociologists and medical services suppliers and civil society.